Case Report: Abscopal effect of radiotherapy in a patient with metastatic duodenal adenocarcinoma and resistance to chemoimmunotherapy - Hao, Yongping; Wang, Jin; Wang, Yinling; Wang, Zihui; Tian, Guangwei; Li, Nan (Frontiers in Immunology, 2025)
BackgroundDuodenal adenocarcinoma is a rare gastrointestinal malignancy, with limited clinical treatment data and a poor prognosis, especially when metastatic. Standard therapies such as chemotherapy and immunotherapy often exhibit limited efficacy, particularly in advanced stages of the disease. The abscopal effect, where local radiotherapy leads to regression of distant metastatic lesions, has been documented in various cancers but is not well explored in duodenal adenocarcinoma. This case report evaluates the potential for radiotherapy to induce an abscopal effect in a patient with metastatic duodenal adenocarcinoma resistant to chemotherapy and immunotherapy.ObjectiveTo explore the potential of radiotherapy to induce an abscopal effect and provide palliative benefits in a patient with advanced, treatment-resistant metastatic duodenal adenocarcinoma.ResultsA 60-year-old female with metastatic duodenal adenocarcinoma, resistant to chemotherapy and immunotherapy, underwent palliative radiotherapy targeting eight metastatic sites. The patient received 40Gy in 20 fractions, completing 19 due to poor physical condition. Notably, radiotherapy resulted in significant regression of a metastatic lesion in the right maxillofacial region, which was not irradiated, demonstrating an abscopal effect. Tumor markers decreased, and the patient experienced substantial pain relief. Immune analysis revealed a decrease in granulocyte and lymphocyte counts and elevated IL-6 levels, which persisted throughout the treatment. Despite this positive response, the patient passed away after 23 months due to disease progression.ConclusionThis is the first reported case of an abscopal effect in metastatic duodenal adenocarcinoma, where radiotherapy not only controlled the primary lesion but also induced regression of distant metastatic lesions. These findings suggest that, for patients with multiple metastases, localized radiotherapy could be a feasible palliative option for pain relief and may provide short-term benefit. Larger studies are warranted to confirm this conclusion.